2010
DOI: 10.1007/s12613-010-0378-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of mixing time in a ladle with dual plugs

Abstract: Based on the two-phase fluid (Eulerian-Eulerian) model, a mathematical model about the gas-liquid flow and mixing behavior was developed to investigate the effect of the offset of dual plugs, the included angle of dual plugs with a center point, and gas flow rate on the mixing time in a ladle with dual plugs. Numerical results indicate that two types of recirculation zones exist in the ladle. One is the middle recirculation between gas and liquid plumes, and the other is the sidewall recirculation between plum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…In previous studies, 6,15,18,22,30) only one electrode was put into certain position of a ladle. However, the electrical conductivity value might vary when the electrode was put at different positions.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, 6,15,18,22,30) only one electrode was put into certain position of a ladle. However, the electrical conductivity value might vary when the electrode was put at different positions.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…In the previous studies, there were two different views about the effect of plug positions on mixing time. Some investigators 6) reported the mixing time varied drastically when the plug moved from 0.5R to the wall, but the tendency was different at various angles. However, the results of Terrazas et al 30) showed that mixing time did not experience major changes when the plug position moved close to the wall.…”
Section: Boundary Conditions and Solution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…José de Jesús VILLELA-AGUILAR, 1) José Ángel RAMOS-BANDERAS, 1) * Constantin Alberto HERNÁNDEZ-BOCANEGRA, 1,2) Antonio URIÓSTEGUI-HERNÁNDEZ, 1) and Gildardo SOLORIO-DÍAZ 3) March 13, 2020) In this work, the multiphase mathematical simulation (steel-argon-slag-air) was used to improve the mixing time in a secondary refining ladle, which is validated with a physical scale model using dye tracer dispertion and measurement of mixing time. An experimental 3 k-p design was performed to optimize the number of cases and analyze the effect of injection gas flow arrangement.…”
Section: Optimization Of the Mixing Time Using Asymmetrical Arrays Inmentioning
confidence: 99%
“…Mixing time (τ mix ) is defined as the time at which there is a chemical homogeneity of 95% in steel. 1) There are several physical and chemical mechanisms involved in mixing, such as molecular diffusion of alloys, turbulent diffusion caused by recirculations and convective flows promoted by steel movement. 2) Argon injection is commonly performed through porous plugs located at the bottom of the ladle, promoting the exchange of momentum from the argon bubbles of the plume.…”
Section: Introductionmentioning
confidence: 99%